2011
DOI: 10.4161/cbt.11.5.14673
|View full text |Cite
|
Sign up to set email alerts
|

Nestin is a novel target for suppressing pancreatic cancer cell migration, invasion and metastasis

Abstract: Nestin, is a class VI intermediate filament (IF) that is expressed in 30% of pancreatic ductal adenocarcinoma (pDaC) cases, and its expression in pDaC positively correlates with peripancreatic invasion. an expression vector carrying a short hairpin RNa (shRNa) targeting nestin was stably transfected into paNC-1 and pK-45h human pancreatic cancer cells, which express high nestin levels. alterations in morphology and alignment of actin filaments and α-tubulin were examined by phase-contrast and immunocytochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 49 publications
10
93
1
Order By: Relevance
“…These features are cellular mechanisms underlying cancer progression and metastasis, and they are also common characteristics found in ATC cells. Recent basic research demonstrated that nestin regulates actin and cell adhesion molecules affecting migration, invasion and metastasis (25). In the present study, however, there were no significant correlations between the expression of nestin in the tumour and the clinicopathological characteristics of the patients, indicating that nestin did not accelerate disease progression in ATC.…”
Section: Univariate Analysis Multivariate Analysis ------------------contrasting
confidence: 53%
“…These features are cellular mechanisms underlying cancer progression and metastasis, and they are also common characteristics found in ATC cells. Recent basic research demonstrated that nestin regulates actin and cell adhesion molecules affecting migration, invasion and metastasis (25). In the present study, however, there were no significant correlations between the expression of nestin in the tumour and the clinicopathological characteristics of the patients, indicating that nestin did not accelerate disease progression in ATC.…”
Section: Univariate Analysis Multivariate Analysis ------------------contrasting
confidence: 53%
“…Furthermore, expression of nestin in PDAC cells was detected in approximately 30% of PDAC cases (22). Recently, we have reported that reduced expression level of nestin in PDAC cells attenuated migration, invasion and metastasis (59). Therefore, nestin may become a new molecular target for both PDAC cells and tumor angiogenesis for nestin-expressing PDAC cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study presents nestin as an inhibitor of invasion, some studies indicate that nestin is a positive regulator of migration and metastasis (Ishiwata et al, 2011b;Kleeberger et al, 2007;Matsuda et al, 2011). Nestin might have contrasting effects on cell function depending on the cell type and transformation stage.…”
Section: Discussionmentioning
confidence: 99%